2008
DOI: 10.4137/cpath.s979
|View full text |Cite
|
Sign up to set email alerts
|

Pathology-Dependent Histological Changes of the Left Stellate Ganglia: A Cadaveric Study

Abstract: Sympathetic hyperinnervation due to nerve sprouting generated by the left stellate ganglion has been noted following cardiopulmonary disease processes. Sympathetic hyperinnervation seems to be limited to cardiopulmonary diseases in the experimental and clinical settings. However, histological changes of the left stellate ganglion following cardiopulmonary diseases in humans have yet to be observed. This study intends to investigate the histological changes of cadaveric sympathetic nervous tissue of left stella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 35 publications
1
14
1
3
Order By: Relevance
“…The decrease in intensity of TH staining in soma of SGNs from CMY patients may appear counterintuitive; however, it likely represents mobilization of enzyme to the nerve terminals to support catecholamine generation and release. In addition to reported structural changes to neurons (25)(26)(27), the findings of the present study support enhanced activity in SGNs in patients with CMY and arrhythmias.…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 64%
“…The decrease in intensity of TH staining in soma of SGNs from CMY patients may appear counterintuitive; however, it likely represents mobilization of enzyme to the nerve terminals to support catecholamine generation and release. In addition to reported structural changes to neurons (25)(26)(27), the findings of the present study support enhanced activity in SGNs in patients with CMY and arrhythmias.…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 64%
“…Our previous research14 demonstrated an increased number of nerve cell bodies within the left stellate ganglia of cadavers with cardiopulmonary disease, in comparison to other pathologies. In the present study, we attempted to present a definite link between an increased number of nerve cell bodies and evidence of previous myocardial infarction.…”
Section: Discussionmentioning
confidence: 85%
“…Since neurons in peripheral ganglia do not replicate (unlike glial cells), this suggests no significant neuronal loss under cardiac pathologic conditions compared to normal. Fibrosis within the stellate ganglia was reported to differ in cadavers with cardiopulmonary disease compared to cadavers without (17). Another study from the same group showed greater neuronal density in stellate ganglia from cadavers with fibrosis detected within the inter-ventricular septum (18).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cardiopulmonary disease have been reported to have greater fibrosis and neuron density within their stellate ganglia than those without such conditions, although the differences were marginal (17, 18). Whether extra-cardiac neurons undergo physical remodeling due to cardiac pathology remains unknown in man.…”
Section: Introductionmentioning
confidence: 99%